High-Order Dimension Synthesis of Planar/Spatial Mechanisms with One-DoF by CAD Variational Geometry. (30th October 2012) - Lu, Yi; Lu, Yang; Ye, Nijia; Yuan, Lin
Abstract : This paper proposes a (computer aided design) CAD variational geometry approach for the high-order dimension synthesis of one-DoF mechanisms based on the given velocity/acceleration of a moving platform along a prescribed trajectory. The objective of this approach is to determine the reasonable dimensions of the mechanisms when given the velocity or/and the acceleration of the moving platform along a prescribed trajectory. First, some concepts and mathematical foundations are explained for constructing the velocity/acceleration simulation mechanism of a general mechanism. Second, the inverse velocity/acceleration simulation mechanisms of the planar/spatial four-bar mechanisms with one-DoF are constructed by the CAD variational geometry. Third, when given the position and the velocity/acceleration of the coupler along a prescribed trajectory, all the reasonable dimensions of the planar/spatial four-bar mechanisms are solved from their simulation mechanisms.